Ownership governance practices and their influence on family businesses financial performance - Betancourt Ramirez, Jose Bernardo (2020)
Ownership was usually a system implicitly assumed in the dynamics of company management, but it deserved more attention than a periodic control in the yearly general shareholder´s assembly. Empowerment of owners was required given the magnitude of decisions made in terms of capital and business purpose, and not just delegating it to the Board or the CEO. Despite the relevance of the topic, a gap was identified in the literature of corporate governance in family business from the ownership dimension. This longitudinal study used a quantitative approach with an explanatory scope that which sought to answer the question: Do shareholders corporate governance practices and family control influence financial performance on businesses? 104 public companies were analyzed and 36.5% of them were identified as family businesses, data were used from National Registry of Values and Issuers, which also responded the country Code 'survey of Colombia in the period 2008 to 2014. Data was processed with Student's t test and Random Effects analysis as a panel data technique. Results shown that family and non-family businesses had significant differences in ownership governance practices, but no significant relationship were identified between corporate governance practices of shareholders or family control with financial performance. The theoretical contribution to the areas of corporate governance and family business was to opening a new scenario for the study of ownership governance; the practical contribution was giving rise to the design of a model of practices for shareholders, where they develop a more active role in terms of capital and strategy decisions that exceeded the decision limits of the Board of Directors; Finally, a contribution in public policy was created by supporting the need to highlight corporate governance practices at the owners level, with models that differentiate Family Business and others.